2021
DOI: 10.1002/mame.202100619
|View full text |Cite
|
Sign up to set email alerts
|

Highly Shrinkable Objects as Obtained from 4D Printing

Abstract: 4D printing of shape memory polymers enables the production of thermoresponsive objects. In this contribution, a facile printing strategy is followed for an in-house synthesized thermoplastic poly(ether urethane). Processing by means of fused filament fabrication, in which the difference between nozzle temperature and material-specific glass transition temperature of the polymer is kept as low as possible, allows to obtain highly shrinkable objects whose shape and thermoresponsiveness can be precisely controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 59 publications
1
24
0
Order By: Relevance
“…4DPed hands‐free door opener made from PEU assembly and its usage illustration (Reproduced with permission. [ 185 ] Copyright 2022, Wiley‐VCH GmbH).…”
Section: Applications Of 4d Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…4DPed hands‐free door opener made from PEU assembly and its usage illustration (Reproduced with permission. [ 185 ] Copyright 2022, Wiley‐VCH GmbH).…”
Section: Applications Of 4d Printingmentioning
confidence: 99%
“…This proposed methodology can be effectively used for developing consumer products. Similarly, Chalissery et al [185] produced highly shrinkable SMP-based materials through FFF process for developing lightweight handsfree door openers for healthcare applications. This 4DPed device shrinked when heated to fit on door handles, permitting an easy assembly as depicted in Figure 16.…”
Section: Other Engineering Applicationsmentioning
confidence: 99%
“…In this way, an approach is pursued in which the so-called “If-Then-Else” relationships apply. Such approaches of self-sufficiently reacting material systems are currently being intensively researched in connection with programmable materials. …”
Section: Introductionmentioning
confidence: 99%
“…[7] In the context of additive manufacturing (AM), the so-called "four-dimensional (4D)-printing" makes it possible to control the shape of an SMP both before and after heating above the DOI: 10.1002/mame.202200214 material-specific switching temperature. [8] This means that in certain cases the classic programming of the 1W SME can be omitted. In other words, 4D-printed objects are thermoresponsive and thus available for immediate use.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Until recently, researchers focused on the implementation of thermoresponsiveness in objects with smaller layer heights (z < 5 mm), where the degree of shrinkage becomes weaker from layer to layer. [8,14] In a recent study, some of us employed an amorphous poly(ether urethane) and PLA for 4D-printing and showed that the technological key to realize distinct shrinkage is keeping the difference between the nozzle temperature and the glass transition temperature (T g ) of the polymers to a minimum possible value. This allows a rapid vitrification of the polymers once deposited on a printing bed.…”
Section: Introductionmentioning
confidence: 99%